Protein Domain Guided Screen for Sequence Specific and Phosphorothioate-Dependent Restriction Endonucleases - Lutz, Thomas; Czapinska, Honorata; Fomenkov, Alexey; Potapov, Vladimir; Heiter, Daniel F.; Cao, Bo; Dedon, Peter; Bochtler, Matthias; Xu, Shuang-yong (Frontiers in Microbiology, 2020)
Modification dependent restriction endonucleases (MDREs) restrict modified DNA, typically with limited sequence specificity (2-4 bp). Here, we focus on MDREs that have an SRA and /or SBD (sulfur binding domain) fused to an HNH endonuclease domain, cleaving cytosine modified or phosphorothioated (PT) DNA. We independently characterized the SBD-SRA-HNH endonuclease ScoMcrA, which preferentially cleaves 5hmC modified DNA. We report five SBD-HNH endonucleases, all recognizing GpsAAC/GpsTTC sequence and cleaving outside with a single nucleotide 3′ stagger: EcoWI (N7/N6), Ksp11411I (N5/N4), Bsp305I (N6/N4-5), Mae9806I (N(8 10)/N(8-9)), and Sau43800I (N(8-9)/N(7-8)). EcoWI and Bsp305I are more specific for PT modified DNA in Mg2+ buffer, and promiscuous with Mn2+. Ksp11411I is more PT specific with Ni2+. EcoWI and Ksp11411I cleave fully- and hemi-PT modified oligos, while Bsp305I cleaves only fully modified ones. EcoWI forms a dimer in solution and cleaves more efficiently in the presence of two modified sites. In addition, we demonstrate that EcoWI PT-dependence has biological function: EcoWI expressing cells restrict dnd+ GpsAAC modified plasmid strongly, and GpsGCC DNA weakly. This work establishes a framework for biotechnology applications of PT-dependent restriction endonucleases (PTDRs).